Recurrent abdominal pain and consulting behaviour among children in a rural community in Malaysia - Boey, Christopher Chiong Meng; Goh, Khean Lee (Elsevier, 2001)
Aim. To look at predictors of consulting behaviour among children with recurrent abdominal pain in a rural community in Malaysia. Subjects and methods. A sample of 1462 school-children aged between 9 and 15 years were randomly selected from all schools in Kuala Langat, a rural district in Malaysia. Those with recurrent abdominal pain, defined according to Apley's criteria, were recruited and divided into consulters and non-consulters. A consulter was defined as a child who had sought the help of a medical practitioner at least once in the past year for recurrent abdominal pain. A detailed clinical, social and family history was obtained in all recruited children. Results. A total of 161 children were recruited: 78 (48.4) consulters, 83 (51.6) non-consulters. Of the consulters, 40 were boys, 38 were girls (male:female ratio = 1.1:1). The two sexes did not show a significant difference in prevalence of consulters (p=0.189). Of the ethnic groups, only Indians had a significantly higher likelihood to consult a doctor (Indians, p=0.006; Malays, p=0.742; Chinese, p=0.050). Younger children (under 12 years) had a significantly higher chance of having been brought to see a medical practitioner (p=0.014). Children in whom age of onset of abdominal pain was below ten years were also more likely to have been seen by a doctor (p=0.012). Children who had consulted a doctor were more likely to be missing school because of abdominal pain (p<0.001). Pain severity was not a significant factor (p=0.429). Multiple logistic regression analysis revealed that the only variable that remained significantly associated with health-care consultation was school absence (p=0.001). Conclusions. Children who saw their doctors for recurrent abdominal pain were also more likely to be those who missed school on account of abdominal pain. Following multiple regression analysis, other factors were no longer significant.